2009
DOI: 10.1111/j.1365-2966.2009.14755.x
|View full text |Cite
|
Sign up to set email alerts
|

Are mergers responsible for universal halo properties?

Abstract: N-body simulations of Cold Dark Matter (CDM) have shown that, in this hierarchical structure formation model, dark matter halo properties, such as the density profile, the phase-space density profile, the distribution of axial ratio, the distribution of spin parameter, and the distribution of internal specific angular momentum follow `universal' laws or distributions. Here we study the properties of the first generation of haloes in a Hot Dark Matter (HDM) dominated universe, as an example of halo formation th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 64 publications
8
75
0
1
Order By: Relevance
“…However, this does not mean that mergers are the only way to generate such distributions. As has been shown recently by Wang & White (2009) even hot dark matter simulations which have almost no mergers show such AMDs. Hence, the origin of the universal form is more generally related to the virialization processes such as the violent relaxation.…”
Section: Discussionsupporting
confidence: 62%
“…However, this does not mean that mergers are the only way to generate such distributions. As has been shown recently by Wang & White (2009) even hot dark matter simulations which have almost no mergers show such AMDs. Hence, the origin of the universal form is more generally related to the virialization processes such as the violent relaxation.…”
Section: Discussionsupporting
confidence: 62%
“…In the past few years, many studies based on Chandra and XMM observations have shown that in general galaxy clusters exhibit elliptical surface brightness maps. Simulations have also predicted that dark matter halos show axis ratios typically of the order of ≈0.8 (Wang & White 2009), thereby disproving the spherical geometry assumption usually adopted (Reiprich & Boringer 2002;Bonamente et al 2006;Shang et al 2009). In this line, the first determination of the intrinsic threedimensional (3D) shapes of galaxy clusters was presented by Morandi et al (2010) by combining X-ray, weak-lensing, and strong-lensing observations.…”
Section: Introductionmentioning
confidence: 96%
“…The Galactic halo forms through a process of hierarchical merging, smooth accretion, and violent relaxation [1,22,23]. The central regions of halos, where relaxation processes have ended, are in quasi-static equilibrium [24].…”
Section: Equilibrium Dark Matter Distributionsmentioning
confidence: 99%